Civil társadalom és szakszervezetek - Tóth, András (Szociológiai Szemle, 2024)
The paper has the objective of exploring and describing the role of trade unions in the development and strengthening of civil society. However, the study of how far the trade unions can be regarded civil social movements is closely associated to it. Several characteristic features of the trade unions link them to the civil social movements. As far as their roots are concerned, they were produced by the self-organisation of employees. The main feature of the trade unions, namely that they represent economic interests in the face of employers, has shaped them different from the civil organisations. The paper argues that the specific contribution of employees’ interest representation to the evolution of civil society can be found within the framework of the system of labour relations. In other words, it is not enough to think in terms of the dichotomy of state and the self-organisation of society, when one wishes to clarify to what extent have the trade unions contributed to the evolution and strengthening of the civil social sphere. The establishment of the legal and political conditions of free combination, the free establishment of the employees’ interest representations, the regained independence, or dissolution of the existing trade unions nationalised, or kept under control earlier, is only one of the con’ditions of the trade unions playing their proper role in the development of civil society. The other- condition is the setting up of new trade unions, independent of employers, and the acquisition of autonomy from the employers by the already existing organisations of employees’ interest representation.